The Role of Educational Administration Supervision in Improving the Quality of School Management - Lia Eviyanti; Miftahudin; Supardi; Agus Gunawan (Jurnal Multidisiplin Madani, 2024)
This study aims to analyze the role of educational administration supervision in improving the quality of school management. The quality of school management is highly dependent on the effectiveness of supervision carried out by the principal, educational supervisor, and administrative staff. In this study, the method used is a literature study, by reviewing various relevant literature, both from books, articles, journals, and policy documents related to educational administration supervision. The analysis was carried out on various theories and practices of supervision related to increasing efficiency, accountability, and transparency in school management. The results of the literature study indicate that educational administration supervision plays an important role in creating an organized and efficient management system, improving managerial quality, and strengthening the capabilities of administrative staff. In addition, challenges identified in the implementation of supervision include the lack of training and professional development for administrative staff, technological limitations, and low levels of collaboration between related parties. As a solution, this study proposes the importance of increasing information technology-based training and developing a data-based and collaborative supervision system to support better school management quality. These findings are expected to contribute to the development of more effective and adaptive educational administration supervision policies and practices